(untitled) (Research, Society and Development, 2020)
Objective: To identify the available evidence about the use of Mindfulness by nursing professionals to reduce stress. Method: The assumptions of the integrative review were used in the databases National library of Medicine and Latin American and Caribbean Literature in Health Sciences. Using articles available in full, online, free, in Portuguese and English, between the years 2015 to 2019. 349 articles were found and 14 were selected, which met the inclusion criteria. Results: Three categories emerged: factors related to the work of nursing professionals that lead to the development of stress; the benefits of Mindfulness in reducing stress; the factors that influence nursing professionals regarding adherence to Mindfulness in their professional practice. Conclusion: the results suggest that nursing professionals, after intervention with the use of Mindfulness meditation, present positive results for the reduction of stress, anxiety and depression.